Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (MedChemComm, 2015)
A number of thieno[2,3-d]pyrimidin-4(3H)-ones were designed, synthesized and screened against Mycobacteria as a part of our program to develop new antitubercular agents. It was observed that some of the compounds have significant antimycobacterial activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743). The active compounds were studied for cytotoxicity against four cell lines and were found to be non-cytotoxic. The results showed that compounds 13b and 29e were found to exhibit very good antimycobacterial activity (MIC in the range of 6-8 mu M) and the thienopyrimidinones as a class have potential to be developed as antitubercular agents.

Synthesis and bioactivity of novel triazole incorporated benzothiazinone derivatives as antitubercular and antioxidant agent - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Arkile, Manisha A.; Khedkar, Vijay M.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and M. bovis BCG, a small focused library of benzothiazinone based 1,2,3-triazoles has been efficiently prepared via click chemistry approach. Several derivatives were found to be promising inhibitors of MTB and M. bovis BCG characterized by lower MIC values (27.34-29.37 mu g/mL). Among all the synthesized compounds, 6c and 6e is the most active compound against MTB and M. bovis BCG. The compounds were further tested for anti-proliferative activity against HeLa, A549 and A431 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activity with IC50 range = 14.14-47.11 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target MTB DprE1, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of the in vitro and in silico study suggest that the triazole incorporated benzothiazinone may possess the ideal structural requirements for further development of novel therapeutic agents. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antioxidant; Antitubercular; Docking study

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents (vol 6, pg 2209, 2015) - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (Medchemcomm, 2016)